2020
DOI: 10.21474/ijar01/12271
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Pulmonary Hypertension in Sickle Cell Anemiai Patient in Ksa

Abstract: Introduction: Pulmonary hypertension (PH) is a relatively common and severe complication of SCI and an independent risk factor for mortality. Sickle cell disease is considered one of the most common diseases in the Kingdom of Saudi Arabia. When a healthy disease related to cardiovascular health is highlighted, sickle cell anemia may be the most common and related disease in high pulmonary pressure. In this study, we aimed in this study to determine prevalence of PHTN in SCA patient, and associated risk factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…In our study, female patients (53.3%) are slightly more than males (46.7%), similar to regional research in Saudi Arabia, which found that females represent 52.2% (4). Also, another study in New York found that females (54.3%) are more than half of the patients (5). Additionally, we found that 29% of the patients have co-existent Thalassemia disorder in contrast to another study which was only 5% (6) (Table 1).…”
Section: Resultssupporting
confidence: 89%
“…In our study, female patients (53.3%) are slightly more than males (46.7%), similar to regional research in Saudi Arabia, which found that females represent 52.2% (4). Also, another study in New York found that females (54.3%) are more than half of the patients (5). Additionally, we found that 29% of the patients have co-existent Thalassemia disorder in contrast to another study which was only 5% (6) (Table 1).…”
Section: Resultssupporting
confidence: 89%